2022
DOI: 10.1093/europace/euac096
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of stroke risk score performance: a systematic review and meta-analysis among 6 267 728 patients with atrial fibrillation

Abstract: Aims Multiple risk scores to predict ischaemic stroke (IS) in patients with atrial fibrillation (AF) have been developed. This study aims to systematically review these scores, their validations and updates, assess their methodological quality, and calculate pooled estimates of the predictive performance. Methods and results We searched PubMed and Web of Science for studies developing, validating, or updating risk scores for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 124 publications
0
19
0
Order By: Relevance
“…In addition, a recent meta-analysis, the PROSPERO clinical trial, highlights the permanent interest in refining risk scores to accurately categorize patients with AF. This systematic review of multiple risk scores confirmed a positive trend (which needs to be calibrated and externally validated) of improved risk prediction favorable to the newer scales compared to the more widely used CHADS 2 and CHA 2 DS 2 -VASc ( 12 ). Taken together, these observations support that the identification of biomarkers that are predictors for risk of MACE should be extended to other organs and systems to achieve the best clinical follow-up in patients with AF.…”
Section: Risk Stratification In Af a Multisystem Diseasementioning
confidence: 60%
“…In addition, a recent meta-analysis, the PROSPERO clinical trial, highlights the permanent interest in refining risk scores to accurately categorize patients with AF. This systematic review of multiple risk scores confirmed a positive trend (which needs to be calibrated and externally validated) of improved risk prediction favorable to the newer scales compared to the more widely used CHADS 2 and CHA 2 DS 2 -VASc ( 12 ). Taken together, these observations support that the identification of biomarkers that are predictors for risk of MACE should be extended to other organs and systems to achieve the best clinical follow-up in patients with AF.…”
Section: Risk Stratification In Af a Multisystem Diseasementioning
confidence: 60%
“…29 Modified-CHADS 2 score demonstrated the best discrimination compared with other scores for predicting ischemic stroke in patients with atrial fibrillation. 5 Moreover, in another study, modified-CHADS 2 score showed good performance across advanced CKD, both for discrimination and calibration, for ischemic stroke risk estimation in atrial fibrillation patients. 12 In the present study, stroke was associated with atrial fibrillation and the presence of central venous catheter.…”
Section: Discussionmentioning
confidence: 96%
“…Newer scores have optimum predictive abilities, but validations and further studies on calibration are essential to approve this. 5 In CHA 2 DS 2 -VASc score, patients receive 1 or 2 points in each component, with a maximum of 9 points (Table S1). The criteria used are congestive heart failure, arterial hypertension (140/90 mmHg or receiving treatment), age (2 points in over 75 years, 1 point if 65-74 years), DM, previous stroke or transient ischemic attack or thromboembolism (2 points), vascular disease (myocardial infarction, peripheral arterial disease, aortic plaque) and gender (1 point if female).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations